Text, Lies, and the Welfare State: The Portrayal of Welfare Recipients in Welfare-to-Work Educational Programs - Jennifer A. Sandlin (Adult Education Research Conference, 2002)
This study explored the ideological messages about welfare recipients promoted in two welfare-to-work programs. It was found that programs are greatly influenced by the unjust stereotypes about welfare recipients upheld in popular rhetoric. It is concluded that critical educators should question these dominant discourses and find ways to promote this questioning in programs.